From Face-to-Screen to Face-to-Face Learning: Students’ Vaccination Status and Willingness for Blended Learning Modality - Obispo, Kristoffer Paul C.; Paguio, Darwin P.; Amarille, Anna Theresa M. (Future Science / FSH-PH Publications, 2023)
The trend of transitioning back to face-to-face classes from an online, virtual, distance learning and other learning modality during the time of pandemic has started in the Philippines. This study aimed to determine the vaccination status, willingness of the students for the resumption of face-to-face classes as well as parental support or approval of the reopening of in-campus classes. Descriptive design is used in this study with the use of online survey as the primary data gathering method. Using a convenience sampling technique, it garnered 1137 responses at a local college in the Olongapo City, Philippines. Based on the survey result, 84.3% of the students are fully vaccinated with one booster shot while 9.4% are fully vaccinated as of the rollout of this survey. Exactly 50% of the students are willing for the resumption of face-to-face classes, 7.7% are willing with the intention to get vaccinated for the resumption of face-to-face classes. It may seem to have low willingness among the student but among respondents, of about 17.2%, are graduating students, will transfer to another school, and will stop for the next academic year. In terms of parental support and/or approval for the resumption of classes, 64.4% of the parents and guardians showed support to the resumption of in-campus face-to-face classes. Lastly, the result of this survey will serve as an input and basis for the preparation of the academic year 2022-2023 for the blended learning modality with shifting schedule of face-to-face classes.